Identification and functional analysis of the DOF gene family in Populus simonii: implications for development and stress response - Cai, Kewei; Xie, Xiaoyu; Han, Lu; Chen, Junbo; Zhang, Jinwang; Yuan, Hongtao; Shen, Jiajia; Ren, Yishuang; Zhao, Xiyang (Frontiers in Plant Science, 2024)
Plant-specific DNA-binding with one finger (DOF) transcription factor family consists of proteins with a preserved DOF domain at their N-termini, crucial in plant species. Nonetheless, our present understanding of the DOF gene family in Populus simonii is still restricted. This research initially pinpointed 41 PSDOF genes in P. simonii genome. The chromosomal localization results revealed that the PSDOF genes is unevenly distributed among 19 chromosomes, with the highest number of genes located on chromosomes 4, 5, and 11. A phylogenetic tree was constructed based on the homology between Arabidopsis thaliana and P. simonii, dividing the 41 PSDOF genes into seven subgroups. The expression patterns of PSDOF genes indicated that specific genes are consistently upregulated in various tissues and under different stress conditions, suggesting their pivotal involvement in both plant development and response to stress. The divergence in the expression patterns of specific PsDOFs was verified by RT-qPCR analysis. Notably, PSDOF35 and PSDOF28 serve as pivotal hubs in the interaction network, playing a unique role in coordinating with other genes within the family. In conclusion, our analysis enhances our comprehension of the functions of the DOF gene family in tissue development and stress responses within P. simonii. These findings provide a foundation for future exploration into the biological roles of DOF gene family.